A Novel Proxy for Tracking the Provenance of Dust Based on Paired E1’-Peroxy Paramagnetic Defect Centers in Fine-Grained Quartz - Dave, Aditi K.; Timar-Gabor, Alida; Kabacińska, Zuzanna; Scardia, Giancarlo [UNESP]; Safaraliev, Nosir; Nigmatova, Saida; Fitzsimmons, Kathryn E. (American Geophysical Union (AGU), 2022)
Crystal lattice defects in quartz have long been exploited for age determination, yet also show potential for sediment provenance studies. Here, we introduce a novel method for tracking aeolian dust provenance by utilizing the natural accumulation of E1’ and peroxy defect centers in quartz. Our approach is based on the previously observed premise that E1’ and peroxy centers arise from Frenkel defect pairs, and that their concentration increases with the age of the quartz-bearing source rock. We propose that these defect centers can be utilized as a characteristic feature of the source rock and consequently, for fingerprinting sediments derived from it. We successfully apply our new protocol to distinguish fine-grained quartz extracted from loess deposits from two regions in Central Asia which are known to derive from different source material of differing age. Our method offers strong potential for identifying variability in source, both spatially and through time down sedimentary sequences.
Keywords: defect centers; electron spin resonance; loess; provenance; quartz